Exploring Oxygen Vacancy Effect in 1D Structural SnIP for CO2 Electro-Reduction to Formate - Bang, Hyeon Seok; Jeon, Jiho; Kang, Jinsu; Ko, Young Jin; Oh, Cheoulwoo; Kim, Hyunchul; Zhang, Xiaojie; Choi, Kyung Hwan; Woo, Chaeheon; Dong, Xue; Yu, Hak Ki; Lee, Woong Hee; et al. (Small, 2024)
1D nanostructures exhibit a large surface area and a short network distance, facilitating electron and ion transport. In this study, a 1D van der Waals material, tin iodide phosphide (SnIP), is synthesized and used as an electrocatalyst for the conversion of CO2 to formate. The electrochemical treatment of SnIP reconstructs it into a web-like structure, dissolves the I and P components, and increases the number of oxygen vacancies. The resulting oxygen vacancies promote the activity of the CO2 reduction reaction (CO2RR), increasing the local pH of the electrode surface and maintaining the oxidative metal site of the catalyst despite the electrochemically reducing environment. This strategy, which stabilizes the oxidation state of the catalyst, also helps to improve the durability of CO2RR. In practice, 1D structured SnIP catalyst exhibits outstanding performance with >92% formate faradaic efficiency (FEformate) at 300 mA cm−2, a maximum partial current density for formate of 343 mA cm−2, and excellent long-term stability (>100 h at 100 mA cm−2 with >86% FEformate). This study introduced a method to easily generate oxygen vacancies on the catalyst surface by utilizing 1D materials and a strategy to improve the durability of CO2RR by stabilizing the oxidation state of the catalyst.
Keywords: 1-d structural; 1-D structures; 1D nanostructures; CO 2 reduction; Electro reduction; Formate; Oxidation state; Reduction reaction; Vacancy effects; ]+ catalyst; 1D structure; CO2 reduction; electrocatalysts; formate; oxygen vacancy